2006
DOI: 10.1016/j.chemosphere.2006.04.061
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical degradation of 4-chlorophenol at nickel–antimony doped tin oxide electrode

Abstract: The effectiveness of a novel nickel-antimony doped tin oxide electrode for electrochemical degradation of organic pollutants was investigated using 4-chlorophenol (4-CP) as a model toxic organic. The experimental results demonstrate that the optimal Ni content was at Ni:Sn=1:500 in atomic ratio in the precursor coating solution, whereas the Sb:Sn ratio was set at 8:500. Using the electrode prepared with the optimal Ni doping ratio for 4-CP degradation, the charge-based efficiencies were up to 89 microg C(-1) f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
54
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(60 citation statements)
references
References 39 publications
6
54
0
Order By: Relevance
“…For all electrodes application in the 4-CP degradation by using both CA and MPA techniques for 2 hours, after each measurement the final concentration of 4-CP was determined spectrophotometrically and the electrochemical efficiency for 4-CP oxidation was obtained based on the equation [13]:…”
Section: Resultsmentioning
confidence: 99%
“…For all electrodes application in the 4-CP degradation by using both CA and MPA techniques for 2 hours, after each measurement the final concentration of 4-CP was determined spectrophotometrically and the electrochemical efficiency for 4-CP oxidation was obtained based on the equation [13]:…”
Section: Resultsmentioning
confidence: 99%
“…The degradation process efficiency (, %) and electrochemical degradation efficiency (E, mg/C· cm 2 ) for organics degradation was determined based on equations (1) and (2) [37,38]:…”
Section: Analytical Proceduresmentioning
confidence: 99%
“…These redox couples can be added to or present in the waste water. In irreversible process, strong oxidants like ozone Wang et al, 2006), chlorine (Panizza & Cerisola, 2003), hydrogen peroxide (Brillas et al, 1996;Brillas et al, 1995;Do & Chen, 1993) and hydroxyl free radicals etc. are generated and in-situ applied to mineralize the organic pollutants.…”
Section: (A)mentioning
confidence: 99%
“…It was found that by incorporating different metal oxides into the Sb-doped SnO 2 coating, the lifetime was significantly increased. Wang et al (2006) and Chen et al (2010) found out that introducing trace amount of nikel into antimony doped tin oxide electrode could enhance its activity toward 4-chlorophenol and phenol degradation. The possible reason may be due to the hybrid effect of electrooxidation and ozone oxidation because ozone could be in-situ generated on this type anode during electrolysis.…”
Section: Tin Dioxide Anode Application In Waste Water Treatmentmentioning
confidence: 99%